The use of classroom management strategies in handling disciplinary problems in the ESL classroom - Muhammad Sophian, Mohd. Alli (Universiti Malaysia Sarawak, UNIMAS, 2008)
Classroom Management encompasses the business of teaching and learning generally. In the teaching process of English Language in the ESL classroom, classroom management can be an obsolete obstacle prior to the usage of it among the ESL teachers specifically when it is used to deal with various types of classroom disciplinary problems. This research was conducted to find out the types of classroom disciplinary problems faced by the ESL teachers in the ESL classrooms. In addition, this research also focused on the use of classroom management strategies by the ESL teachers in classroom disciplinary problems in the ESL classroom. The ESL teachers from six urban secondary schools from the Kuching Division were involved in this research. There was one instrument used to collect the data for this research: a structured interview. The findings of the research revealed that most of the types of classroom disciplinary problems fall under the type of aggression. Hence, the ESL teachers suggested that the classroom management strategies used should be in line with the proficiency level of the students. This is because every ESL teacher has students with different abilities.